2008
DOI: 10.1007/s00418-008-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and nuclear antigen preservation after high-pressure freezing/freeze-substitution and low-temperature LR White embedding of HeLa cells

Abstract: A protocol for high-pressure freezing and LR White embedding of mammalian cells suitable for fine ultrastructural studies in combination with immunogold labelling is presented. HeLa S3 cells enclosed in low-temperature gelling agarose were high-pressure frozen, freeze-substituted in acetone, and embedded in LR White at 0 degrees C. The morphology of such cells and the preservation of nuclear antigens were excellent in comparison with chemically fixed cells embedded in the same resin. The immunolabelling signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…For immunogold labeling, sections on gilded copper grids were treated as described previously (Philimonenko et al 2002;Strádalová et al 2008). Primary antibodies used were: mouse monoclonal anti-histone H1 IgG antibody, clone AE-4 (Abcam, Cambridge, UK; 5 lg/ml); mouse monoclonal anti-DNA IgM antibody, clone AC-30-10 (Millipore, Billerica, MA, USA; 1 lg/ml).…”
Section: Immunolabeling and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunogold labeling, sections on gilded copper grids were treated as described previously (Philimonenko et al 2002;Strádalová et al 2008). Primary antibodies used were: mouse monoclonal anti-histone H1 IgG antibody, clone AE-4 (Abcam, Cambridge, UK; 5 lg/ml); mouse monoclonal anti-DNA IgM antibody, clone AC-30-10 (Millipore, Billerica, MA, USA; 1 lg/ml).…”
Section: Immunolabeling and Antibodiesmentioning
confidence: 99%
“…Till now, LR White has not been used so widely despite its easy usage and comparatively higher safety in handling (Newman and Hobot 1989). LR White has been shown to be suitable for embedding the mammalian cells both after chemical fixation (Bowes et al 2007;Ghrebi et al 2007;Huang and Zhang 2007;Philimonenko et al 2002) and when combined with high-pressure freezing (Sawaguchi et al 2003;Strádalová et al 2008;von Schack et al 1993). Hess (2003) considered LR White embedding as an acceptable compromise between the intensity of immunolabeling, stability of the sections, preservation of an ultrastructure and safety for health.…”
Section: Introductionmentioning
confidence: 96%
“…The authors concluded that the described methods may lead to precise models of macromolecular assemblies in situ, and thus further our understanding of the function of complex cellular structures. An example for the application of the method for immunoelectron microscopy was given by Stradalova et al (2008) in their investigation of the ultrastructural and nuclear antigen preservation in HeLa cells subjected to high pressure freezing/freeze-substitution and low-temperature LR White embedding. Compared to chemically Wxed cells embedded in the same resin, the morphology of cryoWxed cells was excellent, and the immunolabelling intensity using anti-DNA, anti-lamin and other antibodies against nuclear antigens was signiWcantly increased.…”
Section: Imaging Systemsmentioning
confidence: 99%
“…It has been well documented that cryo-fixation by HPF combined with FS and resin embedding can significantly improve the preservation of ultrastructure and antigenicity [123,124]. Nevertheless, not all antigens can be immunolabelled in such a way due to a limited number of accessible antigens at the resin section surface (especially important in locating rare antigens) [125].…”
Section: At the Edge Of Possibilities -Hybrid Techniquesmentioning
confidence: 99%